Chiral Plasmons Enable Coherent Vortex Smith–Purcell Radiation. Issue 1 (26th October 2022) - Zhang, Zi‐Wen; Zhu, Juan‐Feng; Du, Chao‐Hai; Gao, Fei; Han, Feng‐Yuan; Liu, Pu‐Kun
Abstract: Recent advances in vortex Smith–Purcell radiation (V‐SPR) have spurred many breakthroughs in the generation of vortex beams for their potential applications in chiral detection, particle acceleration, communication, and imaging. However, advanced multi‐mode applications of the V‐SPR suffer from the incoherent spectrum and poor purity in producing high‐order topological charges. Here, by exploiting the rotational symmetry and Brillouin‐folding phenomenon, it is proved that the coherent V‐SPR with independently steerable high‐order topological charge is directly emitted from chiral spoof surface plasmons. Moreover, both topological charges and operation frequencies can be readily tuned, thus enabling flexible adaptability over a broad bandwidth. A proof‐of‐concept prototype is designed and fabricated in the microwave regime, in which the method is demonstrated from the perspective of symmetry and tunability. The proposed methodology can be exploited as a platform to investigate the interaction between chiral plasmons and swift electrons, promising a feasible scheme for generating coherent and tunable vortex beams from the microwave to the terahertz band. Abstract : Considering the vorticity nature of chiral spoof surface plasmons, the coherent vortex Smith–Purcell radiation with steerable topological charge and flexible tunability is reported by customizing the rotational symmetry of electron beams. This work can be exploited as a platform to investigate the interaction between chiral plasmons and swift electrons, paving the way toward robust and tunable vortex beam sources.